The Influence of Organizational Commitment and Empowerment on Employee Performance at the Ternate City Agriculture Service - Slamet, Andri Ningsih; Husen, Zulaiha; Abdurrahman, Ahmad Yani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted with the aim of knowing and analyzing the effect of organizational commitment and empowerment on employee performance. The population in this study were civil servants at the Ternate City Agriculture Service. Data collection in this study used a questionnaire which was distributed to 55 respondents who worked as employees at the Ternate City Agriculture Service. The results of this study indicate that; (1) organizational commitment has a positive and significant effect on employee performance, meaning that the higher organizational commitment, the higher the performance produced by employees, (2) empowerment has a positive and significant effect on employee performance, meaning that the higher the empowerment, the higher the performance produced by employees, (3) organizational commitment and empowerment have a positive effect simultaneously on the performance of employees at the Agriculture Service Office of the City of Ternate. The test tool used is multiple linear regression analysis using the statistical package for social scientists (SPSS) 25.0 as the test tool.